Broccoli Myrosinase cDNA Expression in Escherichia coli and Saccharomyces cerevisiae - Carolina Curiqueo; Andrea Mahn; Antonio Castillo (Biomolecules, 2022)
Myrosinases (EC 3.2.1.147) are enzymes known for the generation of hydrolysis products that have a potential beneficial effect on human health. Their reaction mechanisms are widely studied, in order to improve and optimize secondary metabolite production processes. In this work, kinetic and biochemical properties of the broccoli myrosinase enzyme produced from its cDNA cloned in Escherichia coli and Saccharomyces cerevisiae were investigated. The results revealed that the thermal stability of the enzyme produced in S. cerevisiae was slightly higher (30 to 60 °C) than that of myrosinase produced in E. coli (20 to 50 °C). The effect of pH on the enzymatic activity was similar in both enzymes, with pH 3 being the optimum value under the reaction conditions used. The kinetic behavior of both enzymes was adjusted to the Michaelis–Menten model. The catalytic efficiency was up to 4 times higher in myrosinase produced in S. cerevisiae, compared to myrosinase produced in E. coli. The glycosylations present in the enzyme would be related to the formation of a dimeric quaternary structure and would not play an essential role in enzymatic activity, since both enzymes were biologically active. These results will probably allow the development of strategies for the production of bioactive metabolites of medical interest.